Aryl derivatives of 3H-1,2-benzoxaphosphepine 2-oxides as inhibitors of cancer-related carbonic anhydrase isoforms IX and XII - Anastasija Balašova; Aleksandrs Pustenko; Alessio Nocentini; Daniela Vullo; Claudiu T. Supuran; Raivis Žalubovskis (Taylor & Francis Group, 2023)
A range of 3H-1,2-benzoxaphosphepine 2-oxide aryl derivatives with various substitution patterns at positions 7, 8, or 9 of the scaffold was synthesised in five steps from the commercially available salicylaldehydes. All of the newly obtained compounds were studied for their inhibition potency against carbonic anhydrase (CA) isoforms I, II, IX, and XII. Delightfully, these compounds showed a striking selectivity for the cancer-associated CA IX and XII over the cytosolic CA I and II, whose inhibition may lead to side-effects. Overall, a structure-activity relationship (SAR) revealed that 7- and 8-substituted aryl derivatives were more effective inhibitors of CA IX and XII than 9-substituted derivatives. In addition, the fluorine-containing analogues emerged as the most potent CA IX/XII inhibitors in this series.